Exposure to television and support for restrictive immigration policies in the midst of the immigration crisis: A cross‐national comparison. (11th November 2021) - Geurts, Nella; Geurts, Roos; Scheepers, Peer; Vergeer, Maurice
Abstract: Objective: This study explored associations between television exposure and public support for restrictive immigration policies in Europe, distinguishing general television exposure from exposure to television news. We explored explanations of generalized social distrust and perceived ethnic threat and, moreover, acknowledged cross‐national variation in asylum applicants. Methods: We applied multi‐level regression analyses using the European Social Survey (2014–2015), covering 19 countries ( n = 29.161). Results: General television exposure and support for restrictive immigration policies related positively, whereas exposure to television news related negatively to these policy preferences. Furthermore, both generalized social distrust and perceived ethnic threat mediated the links between both forms of exposure and these preferences. An increase in the number of asylum applicants strengthened the positive relationship between general television exposure and these policy preferences. Conclusions: This study provides new insights into the role of individual and national factors for support for restrictive immigration policies from a contemporary and cross‐national perspective.